2007
DOI: 10.1042/bj20070282
|View full text |Cite
|
Sign up to set email alerts
|

The epigenetic signature of CFTR expression is co-ordinated via chromatin acetylation through a complex intronic element

Abstract: The CFTR (cystic fibrosis transmembrane conductance regulator) gene is a tightly regulated and differentially expressed transcript in many mucosal epithelial cell types. It appears that DNA sequence variations alone do not explain CFTR-related gastrointestinal disease patterns and that epigenetic modifiers influence CFTR expression. Our aim was to characterize the native chromatin environment in cultured cells for intestinal CFTR expression by determining the relationship between histone acetylation and occupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 42 publications
6
40
0
Order By: Relevance
“…Mechanistic studies have shown that the activation of intestinal CFTR by histone acetylation was mediated by transcription factors hepatic nuclear factor 1␣, Cdx2, and Tcf4, which converge to modify chromatin architecture. These studies suggest a therapeutic potential for inhibition of HDAC activity in increasing CFTR expression (Paul et al, 2007).…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…Mechanistic studies have shown that the activation of intestinal CFTR by histone acetylation was mediated by transcription factors hepatic nuclear factor 1␣, Cdx2, and Tcf4, which converge to modify chromatin architecture. These studies suggest a therapeutic potential for inhibition of HDAC activity in increasing CFTR expression (Paul et al, 2007).…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…3,7,18 Conversely, CFTR transcription was suppressed by repressors that were associated with HDAC activities. 18 The present work shows that similar dynamic changes of histone acetylation occur in regulatory sequences of CFTR in human tissues.…”
Section: Discussionmentioning
confidence: 99%
“…2). [7][8][9][10][11] We analyzed whole blood cells and tissue samples from pancreas, colon, and lung. Samples were collected in three healthy adult donors.…”
Section: Dna Methylation Of Cftr Increases In a Subset Of Cells Durinmentioning
confidence: 99%
See 2 more Smart Citations